A double‐blind randomized trial on subendometrial injection of vasopressin to control bleeding in postpartum hysterectomy due to abnormally invasive placenta. Issue 2 (9th February 2021) - Ghotbizadeh Vhdani, Fahimeh; Nasiri Khormoji, Najmeh; Eftekhar, Negar; Deldar Pasikhani, Maryam; Hantoushzadeh, Sedigheh; Ghamari, Azin; Panahi, Zahra
Abstract: Objective: To investigate the effect of subendometrial vasopressin injection in patients with abnormally invasive placenta (AIP), who underwent cesarean section and hysterectomy. Methods: This randomized double‐blinded clinical trial was conducted on pregnant women diagnosed with AIP grade 4 and 5 by ultrasonography during cesarean section. Women were randomly divided into two equal groups including group 1 (vasopressin) and group 2 (control) who underwent 20 units of vasopressin and 20 cc normal saline injection, respectively. Vasopressin and placebo were injected subendometrially 1 cm medial to the uterine vessels into the lower uterine segment. The exclusion criteria include presence of myocardial infarction, cardiomyopathy, congestive heart failure, uncontrolled hypertension, chronic obstructive pulmonary disease, pelvic malignancy. The outcome of the study was total quantitative blood loss during the cesarean section. We estimated blood loss by measuring the blood volume in one of the suction bottles with addition for weight changes of mops, pads, and soaked linen savers. Results: Sixty patients were recruited into the study, 30 as the vasopressin group and 30 as the controls; with no excluded case. The amount of bleeding in the vasopressin group was significantly lower compared with that in the control group ( P  < 0.001). In the vasopressin group, 83.4% of patients had bleeding of less than 1.5 L, while only 3.3% of the control women had bleeding of less than 1.5 L (relative risk = 5). In addition, the number of injected packed cells was lower in the vasopressin group ( P  < 0.001). Conclusion: It was shown that vasopressin injection can help prevent excess hemorrhage and the subsequent risks of anemia or blood transfusions during abdominal hysterectomy in women with AIP. Synopsis: Vasopressin injection can help prevent excess hemorrhage and the subsequent risks of anemia or blood transfusions in abdominal hysterectomy.